Wear promoted in the apical third of simulated canals after instrumentation with protaper universal system - Kathrein Tapia da Silva; Renata Grazziotin-Soares; Orlando Limongi; Luis Eduardo Duarte Irala; Alexandre Azevedo Salles (Journal of Applied Oral Science, 2009)
OBJECTIVE: This study evaluated the wear in the apical third of simulate canals after preparation with ProTaper Universal Rotary System. MATERIAL AND METHODS: 24 sets of instruments were used in 24 simulated canals in transparent epoxy resin blocks with degree of curvature of either 20°or 40°. The canals were photographed preoperatively and after preparation of the apical stop with ProTaper F3, F4 and F5 instruments. The initial and final images were exported to Adobe Photoshop® software and superimposed to detect the root canal wall differences (in mm) between them, in two points located 1 (A) and 5 (B) mm from the point where the working length was established. Data were subjected to analysis of variance to verify the existence of interaction among the factors: canal curvature, instrument size and curve location. Significant level was set at 5%. RESULTS: Regardless of the location and the canal curvature, F4 and F5 instruments produced the greatest wear (p<0.05). CONCLUSIONS: There was a deviation from the original pathway towards the outside of the root curvature in both analyzed points. All instruments produced canal transportation, but the F4 and F5 instruments produced more than the other instruments, and should thus be used with care in curved canals.